Effectiveness of MTA apical plug in dens evaginatus with open apices - Khoa Van Pham; Thu Anh Tran (BMC Oral Health, 2021)
Abstract Background The present study aims to evaluate the effectiveness of mineral trioxide aggregate (MTA) application in treating dens evaginatus affected teeth with apical lesions and open apices using haemostatic collagen membrane to prevent the apical extrusion of MTA. Methods Twelve patients with 14 dens evaginatus affected teeth with apical lesions and open apices were treated with MTA apical plug and haemostatic collagen membrane. Clinical symptoms of subjective pain, pain of palpation, percussion, sinus tract, and the apical lesions' radiographic parameter were recorded at every 3-month interval up to 9 months after treatment. Paired t-test or Wilcoxon signed-rank test was used for statistical analysis with P < 0.05 as the threshold for considering results to be statistically significant. Results No patient experienced clinical symptoms 3 months after endodontic treatment. In addition, there was a significant difference in the dimensions of the apical lesions' before compared to 3 months after endodontic treatment. Conclusions The combination of MTA apical plug and haemostatic collagen membrane effectively treated dens evaginatus affected teeth with apical lesions, and open apices.